2019
DOI: 10.13057/biodiv/d200920
|View full text |Cite
|
Sign up to set email alerts
|

Variation of seed sizes and its effect on germination and seedling growth of mahogany (Swietenia macrophylla)

Abstract: Abstract. Pramono AA, Syamsuwida D, Putri KP. 2019. Variation of seed sizes and its effect on germination and seedling growth of mahogany (Swietenia macrophylla). Biodiversitas 20: 2576-2582. To get high-quality seeds, the size of seed is often suggested to be criteria of selection in seed collection. However, the size is not always effective to be used as a basis for seed selection. The study is aimed to determine the variation of mahogany (Swietenia macrophylla) seed sizes and its effect on the germination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
1
0
4
Order By: Relevance
“…The best performance obtained for large seed on speed and percentage germination may be due to its large surface area that is better exposed to conditions necessary for germination than small seeds. Previous studies have reported that large seeds outgrow small seeds in seedling production; they produce seedlings that emerge faster and bigger in size in crops like Gmelina arborea (Owoh et al, 2011), Peanut (Steiner et al, 2019), Hairy vetch (Ekpo, 2004), Swietenea macrophylla (Pramono et al, 2019), and Afzelia quanzensis (Mtambalika et al, 2014). However, this result slightly varied with the report of Souza and Fagundes (2014) on Copaitera langsdorffi, which observed that while large seed had higher percentage germination and vigorous seedlings, small seed emerged faster.…”
Section: Discussionmentioning
confidence: 92%
“…The best performance obtained for large seed on speed and percentage germination may be due to its large surface area that is better exposed to conditions necessary for germination than small seeds. Previous studies have reported that large seeds outgrow small seeds in seedling production; they produce seedlings that emerge faster and bigger in size in crops like Gmelina arborea (Owoh et al, 2011), Peanut (Steiner et al, 2019), Hairy vetch (Ekpo, 2004), Swietenea macrophylla (Pramono et al, 2019), and Afzelia quanzensis (Mtambalika et al, 2014). However, this result slightly varied with the report of Souza and Fagundes (2014) on Copaitera langsdorffi, which observed that while large seed had higher percentage germination and vigorous seedlings, small seed emerged faster.…”
Section: Discussionmentioning
confidence: 92%
“…La diferencia entre el número de semillas por kg de los árboles 4, 5 y 6 con los árboles 1, 2 y 3 fue de 14 030 semillas, y con relación a las semillas de los árboles 8, 9 y 10 fue de 23 779. Resultados contrastantes señalan Arce-Cordova et al (2018) para 30 sitios, de los cuales 25 presentaron un promedio de 43 946 semillas y en cinco 78 846 semillas kg -1 , en altitudes de 500 a 1 000 m. En cambio, el número de semillas difiere a los registrados por Espitia-Camacho et al (2017), quienes consignan 94 965 semillas kg -1 en lotes comerciales a una altitud de 13 y 50 m. La variación en el número de semillas puede estar influenciada por la constitución genética de los árboles y por la disponibilidad de nutrientes (Pramono et al, 2019).…”
Section: Análisis Físico De Semillasunclassified
“…La relación positiva registrada en P. mexicana entre el tamaño de las semillas y la germinación coincide con la reportada en especies como Beilschmiedia assamica, Canarium strictum, Dipterocarpus macrocarpus, Ostodes paniculata (Deb y Sundriyal, 2017), Swietenia humilis Zucc. (Calixto Valencia et al, 2022), S. macrophylla (Pramono et al, 2019) y Enterolobium contortisiliquum (Trindade-Lessa et al, 2015), pero a su vez contrasta con la respuesta mostrada en otros taxones cuyas semillas de menor tamaño o peso tienden a germinar mejor (Murali, 1997), aunque incluso hay taxones, como Coulteria platyloba, Dalbergia congestiflora, Mimosa benthamii, Pithecellobium acatlense, en los que la germinación es independiente del peso o tamaño de las semillas (González-Vélez et al, 2020). Esta divergencia de respuestas ha sido difícil de explicar debido a que las variaciones en el tamaño o peso de las semillas y sus repercusiones en la germinación o emergencia son un efecto coyuntural de condicionantes genéticos (Khurana y Singh, 2001;Norden et al, 2009), ambientales o fisiológicos que afectan el éxito reproductivo de cada fuente parental y consecuentemente la formación y tasa de desarrollo de las semillas (Bareke, 2018).…”
Section: Actaunclassified
“…(Lauraceae), Canarium strictum Roxb. (Burseraceae), Dipterocarpus macrocarpus Vesque (Dipterocarpaceae), Ostodes paniculata Blume (Euphorbiaceae) (Deb y Sundriyal, 2017), Swietenia macrophylla King (Meliaceae) (Pramono et al, 2019) y Enterolobium contortisiliquum (Vell.) Morong (Fabaceae) (Trindade-Lessa et al, 2015) la germinación es independiente del tamaño o peso de las semillas (González-Vélez et al, 2020).…”
Section: Introductionunclassified